The Relevance of Regenerating Gene 1a Polymorphisms to Radiation Sensitivity and Survival of Nasopharyngeal Carcinoma Receiving Radiotherapy in a Southern Chinese Population - Xing HJ; Chen XD; Sun HX; Dai YZ; Han YF; Chen HB; Liu F (Dove Medical Press, 2021)
Hai-Jie Xing,1,*,2 Xiang-Dong Chen,3,* Hong-Xia Sun,4,* Yao-Zhang Dai,5,* Yao-Feng Han,6,* Hai-Bo Chen,7,* Feng Liu8,9,* 1Department of Otorhinolaryngology, Head and Neck Surgery, University of Chinese Academy of Sciences, Shenzhen Hospital, Shenzhen, 518106, People's Republic of China; 2Department of Otorhinolaryngology Head and Neck Surgery, Affiliated Xinhua Hospital of Hainan Medical Colleage, Haikou, 570311, People's Republic of China; 3Department of Otolaryngology, Head and Neck Surgery, Affiliated General Hospital of Shenzhen University, Shenzhen, 518106, People's Republic of China; 4Wuhan Medical Science Research Institution, Wuhan, 430013, People's Republic of China; 5Department of Throat, Head and Neck Surgery, Affiliated Otolaryngological Hospital, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450052, People's Republic of China; 6Department of Epidemiology, Public Health College of Xiamen University, Xiamen, 361005, People's Republic of China; 7Clinical Laboratory, Affiliated Xinhua Hospital of Hainan Medical Colleage, Haikou, 570311, People's Republic of China; 8Department of Endocrine Oncology, University of Chinese Academy of Sciences, Shenzhen Hospital, Shenzhen, 518106, People's Republic of China; 9Department of Medical Imaging Centre, The First Affiliated Hospital, Jinan University, Guangzhou, 510630, People's Republic of China*These authors contributed equally to this workCorrespondence: Hai-Jie XingDepartment of Otorhinolaryngology, Head and Neck Surgery, University of Chinese Academy of Sciences, Shenzhen Hospital, Shenzhen, 518106, People's Republic of ChinaTel/Fax +86-755-27548815Email 1349170050@qq.comXiang-Dong ChenDepartment of Otolaryngology, Head and Neck Surgery, Affiliated General Hospital of Shenzhen University, Shenzhen, 518106, People's Republic of ChinaTel/Fax +86-755-27548815Email chenxiangd_dr55@163.comObjective: Gene polymorphism is closely related to tumor development, therapeutic response and prognosis. The relationship between regenerating gene 1A (Reg1A) polymorphism and nasopharyngeal carcinoma (NPC) is unclear. This retrospective study aimed to analyze the association between Reg1a polymorphisms and metastasis, radiation sensitivity and survivals in patients with NPC.Methods: A total of 308 patients who had received radiotherapy at the Affiliated Xinhua Hospital, Hainan Medical College, between January 2010 and December 2018 with NPC, were enrolled for assessment of Reg1a polymorphisms through direct DNA sequencing.Results: In the polymorphism of gene REG1A, patients with rs10165462 20CC genotype had later T stages (OR = 4.051, 95% CI: 1.775- 9.244, P = 0.001), whereas carriers with rs12072 2922CC genotype had earlier T stages (OR = 1.891, 95% CI: 1.018- 3.514, P = 0.044) after adjustments for age and gender, respectively. Among rs10165462 20 C/T polymorphism, 20TT wild-type was associated with better radiation response (P = 0.0019), and multivariate analysis showed that it was the only genotype of polymorphism that was significantly associated with better radiation response (OR = 0.265, 95% CI: 0.096- 0.727, P = 0.01). Patients with the 20TT wild-type had a better five-year overall survival (60.9%) rate and five-year progression-free survival (60.8%) than those with the 20CC genotype (41.8% and 39.4%, P = 0.01 and P = 0.004, respectively). Patients with variant alleles (CC + CT) had significantly poorer OS (45.2%) and PFS (41.8%) compared with wild-type (TT) carriers (60.9% and 60.8%; P = 0.037 and P = 0.015, respectively). As for rs12072, patients with variant alleles (TT + TC) had significantly adverse OS and PFS compared with wild-type (CC) carriers (62.5% vs 44.8% and 62.5% vs 42.9%; P = 0.024 and P = 0.027, respectively). Cox regression showed that rs10165462 20CT was the only prognostic factor for OS (HR = 1.642, 95% CI 1.038- 2.598, P = 0.034) and PFS (HR = 1.705, 95% CI 1.080- 2.692, P = 0.022).Conclusion: Reg1a polymorphisms may be a predictor of radiation response, local invasion, OS and PFS in patients with NPC who undergo radiotherapy treatment.Keywords: regenerating gene 1a, polymorphisms, radiation, sensitivity, nasopharyngeal, survival